Irritable bowel syndrome - pathophysiology, diagnosis, treatment. The role of low FODMAP diet - Gąbka, Ilona; Dalmata, Weronika; Dąbrowski, Jan; Szarpak, Julita; Lipiec, Marta (Journal of Education, Health and Sport, 2022)
Introduction: The gut microbiota is the microorganisms in the digestive tract. They are mainly bacteria. They play a very important role in maintaining the body’s homeostasis. The state of the microbiota is influenced by lifestyle including diet, stress and physical activity. In irritable bowel syndrome, there are disorders in the composition of the intestinal microbiota. It is also associated with a disruption in the proper functioning of the gut-brain axis. Aim: The aim of this study was to review the literature reports on irritable bowel syndrome and the impact of a low FODMAP diet. Methods: Data for the article were retrieved using PubMed setting the time descriptors to 2017-2021. Results and conclusions: Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disease. It is manifested by chronic abdominal pain , diarrhea or constipation and changes in the frequency of bowel movements. It significantly affects the quality of life of patients. The diagnosis uses the Roman IV criteria. Pharmacological as well as non-pharmacological methods are important in the treatment. A low-FODMAP diet plays a major role. Studies show that its proper use significantly alleviates the symptoms of IBS.